2007
DOI: 10.1152/jn.00513.2006
|View full text |Cite
|
Sign up to set email alerts
|

Duration-Dependent Response of SI to Vibrotactile Stimulation in Squirrel Monkey

Abstract: In previous studies, we showed that the spatial and intensive aspects of the SI response to skin flutter stimulation are modified systematically as stimulus amplitude is increased. In this study, we examined the effects of duration of skin flutter stimulation on the spatiotemporal characteristics of the response of SI cortex. Optical intrinsic signal (OIS) imaging was used to study the evoked response in SI of anesthetized squirrel monkeys to 25-Hz sinusoidal vertical skin displacement stimulation. Four stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
51
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 28 publications
5
51
0
Order By: Relevance
“…Delivery of adapting stimuli to both of the sites of skin stimulation prior to simultaneous delivery of the test and standard stimuli, however, leads to an improvement in amplitude discrimination performance -a finding which is consistent with prior published psychophysical studies that demonstrate improvements in discriminatory capacity with much longer durations of adaptation. Striking parallels between the results obtained in this study and those reported in a prior study of the effects of vibrotactile adaptation on the optical response of squirrel monkey contralateral SI cortex to vibrotactile stimulation (Simons et al, 2007;Simons et al, 2005) suggest that the perceptual effects detected in this study could be attributable to adaptationinduced alterations of SI response. …”
supporting
confidence: 90%
See 2 more Smart Citations
“…Delivery of adapting stimuli to both of the sites of skin stimulation prior to simultaneous delivery of the test and standard stimuli, however, leads to an improvement in amplitude discrimination performance -a finding which is consistent with prior published psychophysical studies that demonstrate improvements in discriminatory capacity with much longer durations of adaptation. Striking parallels between the results obtained in this study and those reported in a prior study of the effects of vibrotactile adaptation on the optical response of squirrel monkey contralateral SI cortex to vibrotactile stimulation (Simons et al, 2007;Simons et al, 2005) suggest that the perceptual effects detected in this study could be attributable to adaptationinduced alterations of SI response. …”
supporting
confidence: 90%
“…Such modifications attain full development within a few tens of milliseconds of stimulus onset, and disappear within seconds after stimulus termination (visual cortical neurons: (Bredfeldt and Ringach, 2002;Celebrini et al, 1993;Das and Gilbert, 1995;DeAngelis et al, 1995;Dinse and Kruger, 1990;Pack and Born, 2001;Pettet and Gilbert, 1992;Ringach et al, 1997;Shevelev et al, 1998;Shevelev et al, 1992;Sugase et al, 1999); for recent review of short-term primary somatosensory cortical neuron dynamics see ). somatosensory (SI) cortex using different amplitudes and durations of vibrotactile stimulation Simons et al, 2007;Simons et al, 2005). Simons et al (Simons et al, 2005) demonstrated that 25 Hz vibrotactile (flutter) skin stimulation at different amplitudes evoked an OIS response confined to the same local region of SI, but the magnitude of response varied proportionally with the stimulus amplitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, observations obtained in the pioneering neurophysiological recording studies led Mountcastle and colleagues to advance the proposal (Mountcastle and Darian-Smith, 1968;LaMotte and Mountcastle, 1975;LaMotte and Mountcastle, 1979) that a subject's ability to localize a mechanical stimulus on the skin depends on stimulus-evoked dynamic (time-dependent) pericolumnar lateral inhibitory interactions which increase the spatial contrast between regions of SI cortex activated differentially by stimulus-evoked afferent drive. The idea that a subject's ability to accurately perceive the spatial locus of a mechanical skin stimulus depends on the spatial contrast of the activity profile that a stimulus evokes in the responding region of contralateral SI cortex has received wide acceptance, but the continuing absence of direct experimental support for this concept motivated us to reevaluate the phenomenon using optical intrinsic signal imaging methods (OIS imaging; Tommerdahl et al, 2002;Simons et al, 2005;Simons et al, 2006) to investigate the effect of different durations of repetitive mechanical stimulation of a skin site on the spatial profile of SI activation. Briefly summarized, we found that exposure of a skin site to a temporally extended (> 0.5 sec) 25 Hz vibrotactile stimulus is consistently accompanied by a dramatic but stereotypical sequence of changes in the global SI activity pattern -while activation in SI initially occurred in much of the extensive region that receives input from the stimulated skin site, with continuing stimulation not only did the activated region shrink in size, but the surviving region of activation came to be bounded by one or more regions where activity was reduced to significantly below-background values (Tommerdahl et al, 2002;Simons et al, 2005;Simons et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The idea that a subject's ability to accurately perceive the spatial locus of a mechanical skin stimulus depends on the spatial contrast of the activity profile that a stimulus evokes in the responding region of contralateral SI cortex has received wide acceptance, but the continuing absence of direct experimental support for this concept motivated us to reevaluate the phenomenon using optical intrinsic signal imaging methods (OIS imaging; Tommerdahl et al, 2002;Simons et al, 2005;Simons et al, 2006) to investigate the effect of different durations of repetitive mechanical stimulation of a skin site on the spatial profile of SI activation. Briefly summarized, we found that exposure of a skin site to a temporally extended (> 0.5 sec) 25 Hz vibrotactile stimulus is consistently accompanied by a dramatic but stereotypical sequence of changes in the global SI activity pattern -while activation in SI initially occurred in much of the extensive region that receives input from the stimulated skin site, with continuing stimulation not only did the activated region shrink in size, but the surviving region of activation came to be bounded by one or more regions where activity was reduced to significantly below-background values (Tommerdahl et al, 2002;Simons et al, 2005;Simons et al, 2006). In addition, evidence obtained in in vivo and in vitro imaging studies indicates unambiguously that GABA-mediated cortical inhibitory processes are responsible for the time-dependent spatial contraction of the SI activation pattern that accompanies the delivery of repetitive thalamocortical afferent drive (e.g., as can be achieved using temporally extended vibrotactile stimulation , or repetitive electrical stimulation of thalamocortical afferents (Kohn et al, 2000)).…”
Section: Introductionmentioning
confidence: 99%